Immunocytochemical detection of Salmonella Gallinarum and Salmonella Pullorum in experimentally infected chickens - PRASANNA, K; PALIWAL, O P; KUMAR, RAM; TRIPATHI, B N (The Indian Journal of Animal Sciences, 2014)
Experimental fowl typhoid (FT) and pullorum disease (PD) were induced by intracrop inoculation of S. Gallinarum and S. Pullorum, respectively, in 1-week-old white Leghorn chicks. The organisms were reisolated by cloacal swab culturing, and their localization in the tissues was detected by immunoperoxidase (IPT) and immunofluorescence (IF) techniques at various intervals. The antigens were also detected in tissues, viz. crop, liver, duodenum, ileocaecal junction and caecum by immunocytochemistry during the intervals when the organisms ceased to be excreted in the faeces and thus can be used to detect the carrier status of the chickens.